Accumulation Profiles of Embryonic Salt-Soluble Proteins in Maize Hybrids and Parental Lines Indicate Matroclinous Inheritance: A Proteomic Analysis - Ning, Fen; Wu, Xiaolin; Zhang, Hang; Wu, Zhaokun; Niu, Liangjie; Yang, Hao; Wang, Wei (Frontiers in Plant Science, 2017)
Maize is one of the most widely cultivated crops. It accumulates a large quantity of seed storage proteins, which are important for seed development and germination, and contribute to the nutritional quality of seeds. Based on solubility, the storage proteins are divided into albumins (water-soluble), globulins (salt-soluble), prolamins (alcohol-soluble), and glutelins (acid- or alkali-soluble). Maize hybrids are cultivated due to the superior performance of F1 hybrids than that of their parents, a phenomenon known as heterosis. However, the accumulation patterns of seed storage proteins in maize embryos between the hybrids and their parental inbred lines have not been compared. In the present study, two elite inbred lines of China, Zheng 58 and Chang 7-2, and their reciprocal hybrids (Zheng 58 × Chang 7-2 and Chang 7-2 × Zheng 58) were used to explore parental influences on the accumulation patterns of seed storage proteins in maize embryos. For this purpose, we focused on seed salt-soluble proteins (SSPs) in our experiments. The SSPs were selectively extracted from maize mature embryos after extensive removal of water-soluble albumin and separated using two-dimensional gel electrophoresis (2-DE), followed by mass spectrometry analysis. Our results indicated that the 2-DE SSP profiles of hybrids closely resembled those of their maternal parent rather than the paternal parent. In other words, 2-DE SSP profiles of Zheng 58 × Chang 7-2 were more similar those of Zheng 58 whereas such profiles of Chang 7-2 × Zheng 58 were more similar to those of Chang 7-2 although the 2-DE profiles of all four maize types were quite similar. In total, 12 relatively abundant SSPs spots representing five kinds of proteins were identified, of which nine protein spots displayed nonadditive accumulation in at least one hybrid. This study provided additional data on dominance and partial dominance effects on maize hybrids embryos. Besides, eariler studies on accumulation profiles of globulin-1 (also known as vicilin), which is one of the most abundant globulins in maize embryos, also support the above results. This study would be helpful in revealing the mechanisms underlying SSPs accumulation patterns in the hybrids.